2010
DOI: 10.1016/j.ijpharm.2010.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Dry powdered aerosols of diatrizoic acid nanoparticle agglomerates as a lung contrast agent

Abstract: Aerosolized contrast agents may improve the resolution of biomedical imaging modalities and enable more accurate diagnosis of lung diseases. Many iodinated compounds, such as diatrizoic acid, have been shown to be safe and useful for radiographic examination of the airways. Formulations of such compounds must be improved in order to allow imaging of the smallest airways. Here, diatrizoic acid nanoparticle agglomerates were created by assembling nanoparticles into inhalable microparticles that may augment depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…The fine particle fraction of the total dose (FPF TD ) was calculated as the percentage of aerosolized particles that reached the lower seven stages of the impactor (corresponding to aerodynamic diameters below 5 µm; stage 2-filter), or the lower five stages (corresponding to aerodynamic diameters below 3 µm; stage 4-filter) (El-Gendy et al, 2010a). …”
Section: Methodsmentioning
confidence: 99%
“…The fine particle fraction of the total dose (FPF TD ) was calculated as the percentage of aerosolized particles that reached the lower seven stages of the impactor (corresponding to aerodynamic diameters below 5 µm; stage 2-filter), or the lower five stages (corresponding to aerodynamic diameters below 3 µm; stage 4-filter) (El-Gendy et al, 2010a). …”
Section: Methodsmentioning
confidence: 99%
“…Many studies reported a decrease of mixing time when precipitation occurred under ultrasound. (25,26) One study showed that ultrasound provided more than 10 times higher mixing rate compared to mechanical stirring. (27) Ultrasound creates bubbles by generating alternate cycles of compression and rarefaction within a liquid.…”
Section: Formulation Of Itraconazole (Itz)mentioning
confidence: 99%
“…The percent emitted fraction (%EF), fine particle fractions of the total dose (FPF TD ), mass median aerodynamic diameter (MMAD), and geometric standard deviation (GSD) were calculated as given below. 14 The %EF was calculated as:…”
Section: Aerosol Characterizationmentioning
confidence: 99%